Impact of Financial Ratios and Company Growth on Sharia Bond Valuation - Ainun Nisa; Ahmad Fauzul Hakim Hasibuan; Nadiatul Muna; Muhammad Fazil (Jurma : Jurnal Program Mahasiswa Kreatif, 2023)
This study aims to examine the impact of profitability, solvency, liquidity and growth on the ratings of sharia bonds listed on the Indonesia Stock Exchange and assessed by PT Pefindo. The population of this study consists of non-financial companies listed on the Indonesia Stock Exchange. The research sample was selected using purposive sampling method. This study uses quantitative methods with data analysis techniques in the form of ordinal logistic regression using SPSS 23. The results show that profitability ratios have a significant positive effect on sharia bond ratings, while liquidity ratios have a significant negative effect. However, the solvency and growth ratios have no effect on sharia bond ratings.